ANALISIS FAKTOR PRODUKSI HASIL TANGKAPAN IKAN CAKALANG (Katsuwonus pelamis) DI PELABUHAN PERIKANAN NUSANTARA SIBOLGA - Ahyar Pulungan; Amanatul Fadhilah (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
The study aims to analyze the factors which influenced the Skipjack Tuna fishing production at the Sibolga Nusantara Fisheries Port. This research was conducted at Sibolga Nusantara Fisheries Port, Central Tapanuli Regency. The research was conducted using a descriptive method with sample of 40 fishermen of purse seine vessels (ship captains) determined through purposive sampling technique. Data analysis techniques were carried multiple linear regression analysis. The results showed that partially, the factors of the fisherman experience, the size of the ship, the power of the engine and the length of the trip had a significant effect on the skipjack tuna fishing production. Meanwhile, the amount of fuel did not have a significant effect. Trip duration was the dominant factor or had a strong influence in the fishing production of skipjack tuna.Keywords: Skipjack Tuna, Production Factor, Sibolga Nusantara Fisheries Port.